Long-term Follow-up After Pediatric Liver Transplantation: Predictors of Growth. Issue 4 (April 2018) - Loeb, Nathalie; Owens, Jillian S.; Strom, Michele; Farassati, Farsad; Van Roestel, Krista; Chambers, Kathryn; Kean, Penni; Ng, Vicky L.; Avitzur, Yaron; Carricato, Megan; Wales, Paul W.; Courtney-Martin, Glenda
ABSTRACT: Objectives: The aim of the study was to describe long-term growth postpediatric liver transplantation and to conduct bivariate and multivariate analysis of factors that may predict post-transplantation growth in children who received a liver transplant from January 1999 to December 2008 at the Hospital for Sick Children. Methods: A retrospective cohort study was conducted with follow-up of up-to 10 years post-transplantation. Mean height and weight z scores and annual differences in mean z scores were plotted against time after transplantation. A 1-way analysis of variance was conducted. Multivariate and univariate Cox proportional hazards analyses were conducted to determine factors associated with reaching the 50th and 25th percentiles for height. Results: A total of 127 children met eligibility criteria. The mean height z score at time of transplantation was −2.21 which by the second year post-transplantation increased significantly to −0.66 (mean increase of 1.55 standard deviation units). There were no further significant increases in mean height z score from 2 years post-transplantation until the end of follow-up at year 10. In multivariate analysis, height at transplant was the most important predictor of linear growth post-transplantation. Conclusions: Children who underwent liver transplantation had significant catch-up growth in the first 2 years post-transplantation followed by a plateau phase. Increased height z-score at transplantation is the most important predictor of long-term growth.